Gender Difference in the Left Coronary Artery: An Angiographic Study. - Vishram Singh; Suresh Babu Kottapalli; Rakesh Gupta; Nitin Agarwal; Yogesh Yadav (Academia Anatomica International, 2020)
Introduction:The prevalence of coronary artery disease in India has led to a rapid transition in health status. Knowledge of coronary artery anatomy including anomalies and variations according to region is very important for clinical therapeutic surgeries. The heart was supplied by two coronary arteries i.e. right and left coronary arteries respectively. Out of two arteries, Left Coronary Artery (LCA) irrigates most of the area of the heart and presents wide variability in its morphology.Subjects and Methods:The present study was carried out in two hundred fifty healthy individuals out of whom one hundred twenty were male. Results:According to division of Left Coronary artery, Bifurcation was seen in 107 males and 111 females. Trifurcation of left coronary artery was seen in seventeen males and twelve females and quadrification was seen in one male and two females. Length of left coronary artery was significantly high in females and diameter was more in males.Conclusion:The findings in this study can help to understand the significant association between the length and angle of division of left coronary artery. The knowledge about anatomy and variations of left coronary artery is very useful for cardiologists to treat clinical complications.